2004
DOI: 10.1103/physrevlett.92.106803
|View full text |Cite
|
Sign up to set email alerts
|

Quantum-Mechanical Investigation of Field-Emission Mechanism of a Micrometer-Long Single-Walled Carbon Nanotube

Abstract: A quantum-mechanical simulation is carried out to investigate the charge distribution and electrostatic potential along a 1 microm long (5,5) single-walled carbon nanotube under realistic field-emission experimental conditions. A single layer of carbon atoms is found sufficient to shield most of the electric field except at the tip where strong field penetration occurs. The penetration leads to a nonlinear decrease of potential barrier for emission, which is equally responsible for the low threshold voltage be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
108
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 161 publications
(112 citation statements)
references
References 20 publications
3
108
0
1
Order By: Relevance
“…A few years ago, it became possible to simulate long CNTs (up to several µm in length) by a hybrid approach involving both quantum mechanics and classical analysis 8,9 . A (5,5) single-walled carbon nanotube (SWCNT) closed with a fullerene hemisphere was simulated in this way (we refer to this as the "closed CNT").…”
Section: Introduction a General Backgroundmentioning
confidence: 99%
“…A few years ago, it became possible to simulate long CNTs (up to several µm in length) by a hybrid approach involving both quantum mechanics and classical analysis 8,9 . A (5,5) single-walled carbon nanotube (SWCNT) closed with a fullerene hemisphere was simulated in this way (we refer to this as the "closed CNT").…”
Section: Introduction a General Backgroundmentioning
confidence: 99%
“…Calculations show that penetration of the electric field is also possible in SWCNTs at the apex region. [25] In our case we used nanotubes with quite a large www.advancedsciencenews.com www.pss-b.com average diameter of 1.8 nm. Since the field penetration may be more efficient for wider nanotubes it can be one of the reasons why saturation effects are rarely observed for FE from clean SWCNTs.…”
Section: Discussionmentioning
confidence: 99%
“…Instead of treating graphene as an ideal metallic sheet, the present paper should take into account the energy band structure and density of states of graphene. More importantly, the field penetration should be considered, as the field penetration would play decisive role in the CFE of nanostructures [24,26]. Based on a self-consistent semiclassical model, we will give the charge distribution (and thus the field penetration) on graphene under the macroscopic applied field analytically.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, sophistic theoretical studies of CFE of nano-structures based on quantum chemistry methods [13][14][15][16][17][18][19][20][21][22][23][24] and electronic band structures [15] do reveal new mechanism and characteristics that are proprietary in nano-strutures. A classical study has indicated that the field emission of nano-sheet follows the ln(J/F 3 )~1/F 2 law in contrast to the conventional FN law of ln(J/F 2 )~1/F.…”
Section: Introductionmentioning
confidence: 99%